THE EFFECT OF HOME PHARMACY CARE EDUCATION ON BLOOD PRESSURE CONTROL AND KNOWLEDGE LEVEL OF HYPERTENSIVE PATIENTS AT KENDALSARI PUBLIC HELATH CENTRE MALANG - Nanang Ardianto; Allis Soraya Setyokanti Winarning; Rudy Mardianto; Ayesi Dewi Safitri (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Hypertension is one of the ten most common degenerative diseases and has a high mortality rate. In 2020, the prevalence of hypertension in Malang City reached 35,641 cases. The role of pharmacists as caregivers in home pharmacy care can help to control hypertension and reduce morbidity. The main objective of this study was to determine the effect of home pharmacy care on hypertension patients’ knowledge and blood pressure management. This study used a quantitative experimental design with a Randomized Control Trial method, with a total of 34 respondents divided into 2 groups: the control group and the test group of 17 respondents each. Using an accidental sampling technique. The research location was Kendalsari Public Health Centre Malang in August 2023. Blood pressure data were measured using a tensimeter, and knowledge level data were obtained using a knowledge questionnaire. Data analysis was performed using paired and pooled t-tests. The results of the analysis of the effect of home pharmacy care on the level of patient knowledge about hypertension with a significance value (2tailed) p = 0.000, and analysis of the effect of home pharmacy care on systolic and diastolic blood pressure with a significance value (2tailed) p = 0.030. The results of this study concluded that home pharmacy care for hypertensive patients had a positive effect on blood pressure control and increased knowledge at the Kendalsari Public Health Center, Malang. Keywords: Home pharmacy care, hypertension, blood pressure control, knowledge level.